The Analysis of the Role of Technological Transformation in Accelerated Local Government Bureaucracy Reform - Ana Suheri; Zulqarnain Zulqarnain; Nurdin I. Muhammad; Ade Risna Sari; Pandu Adi Cakranegara (Universitas Medan Area, 2023)
This paper to discuss the role of technological transformation in accelerating bureaucratic reform in both the central and regional governments in the era of autonomy. In particular, we would explain the digital technology to service public needs, Basic Concepts of E-Government, sub-chapter on the stages of Bureaucratic Transformation and the impact of reform on public services. There needed to be more data discussing the role of technology in accelerating bureaucratic reform. We obtained scientific evidence from a series of electronic searches of the literature, books, and other academic works. To obtain valid data, we investigate it using a phenomenological method., which involves, among other things, an in-depth evaluation data testing system; concluding begins with an interpretation of the data so that it genuinely answers the study problem. After discussing in-depth findings, we can conclude that the role of technological transformation in accelerating local government bureaucratic reform in Indonesia is a solution that has a very positive impact on all public services. This is due to technology's ability to innovate and transform public service tasks that are increasing and being compared. In addition, we also found that the digital technology to service public needs, the basic concepts of E-Government, the stages of bureaucratic transformation and the impact of reform on public services as located in finding section. Hopefully, these findings will be useful in future studies of technology and public services, particularly government bureaucracy.